2012
DOI: 10.1177/0954405411424001
|View full text |Cite
|
Sign up to set email alerts
|

Time, cost, and quality trade-offs in material requirements planning using fuzzy multi-objective programming

Abstract: In this paper, three simultaneous objectives -material requirements planning (MRP) completion time minimization, total cost minimization, and maximization of the quality of raw materials in an MRP system -are balanced by using a fuzzy multi-objective programming (F-MOP) model. Crashing the total MRP completion time; that is, reducing the time by increasing the resources, can improve on-time delivery to the customer. The goal is to determine the optimum crashing in an MRP context such that maximum total satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Furthermore, constraints presented in equations (23) to (27) are rewritten based on equation 28as equations (29) to (39).…”
Section: A: Goal Programming Modelmentioning
confidence: 99%
“…Furthermore, constraints presented in equations (23) to (27) are rewritten based on equation 28as equations (29) to (39).…”
Section: A: Goal Programming Modelmentioning
confidence: 99%
“…In a multi-objective model, several objectives have to be simultaneously optimized considering different membership functions [25], as model (3):…”
Section: Fuzzy Multi-objective Linear Programmingmentioning
confidence: 99%
“…Using the approaches given by [25] and [26], the above mentioned model can be transformed to a constrained single objective model (4). (5) - (7) (using Eq.…”
Section: Fuzzy Multi-objective Linear Programmingmentioning
confidence: 99%
“…Many researchers have employed the fuzzy programming technique to deal with the multi-objective problem by considering the preferences of decision makers in several production planning fields. [25][26][27][28] A number of studies have reported on the progress based on fuzzy programming for the specific applications of production planning. Selim et al 29 and Jamalnia and Soukhakian 30 studied the fuzzy goal programming approach to solve the multi-objective problem in the distribution planning of supply chain and aggregate production planning, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%